2018
DOI: 10.1111/anec.12586
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum cotinine levels and electrocardiographic left atrial abnormality

Abstract: Elevated serum cotinine levels are associated with an abnormal DTNPV1. This suggests that nicotine exposure can lead to left atrial abnormalities, a possible mechanism for increased risk of CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Moreover, our results suggest that nicotine in e-cigarettes may both acutely and chronically shorten ventricular repolarization while also acutely increasing atrial pressures (indicated by P amplitude). Notably, a few studies also observed an increased P amplitude among smokers at baseline [212,213,362,363], similar to our findings in which cotinine (proxy for tobacco use) was associated with P amplitude (particularly in deep terminal negativity of the P wave in V1 [DTNPV1]) in the chronic state [364]. However, the mechanisms for abnormal P wave indices during acute and chronic exposure may differ while also carrying different prognostic value.…”
Section: Resultssupporting
confidence: 87%
“…Moreover, our results suggest that nicotine in e-cigarettes may both acutely and chronically shorten ventricular repolarization while also acutely increasing atrial pressures (indicated by P amplitude). Notably, a few studies also observed an increased P amplitude among smokers at baseline [212,213,362,363], similar to our findings in which cotinine (proxy for tobacco use) was associated with P amplitude (particularly in deep terminal negativity of the P wave in V1 [DTNPV1]) in the chronic state [364]. However, the mechanisms for abnormal P wave indices during acute and chronic exposure may differ while also carrying different prognostic value.…”
Section: Resultssupporting
confidence: 87%
“…induced by nicotine exposure, implies more gateways for the SARS-CoV-2 virus. Moreover, it is possible to hypothesize that SARS-CoV-2 entry and replication may be facilitated or induced through mechanisms related to nAChR mediated-pathways, all converging to ACE2 regulation and signalling [15,25].Additionally, nicotine exposure induces a pro-thrombotic state via stimulation of tissue factor (TF) expression both in endothelial cells and smooth muscle cells [26] as well as neo-angiogenesis [27] and, finally, elevated serum cotinine levels, the metabolite of nicotine, are associated with left atrial abnormalities, a possible mechanism for increased risk of cardiovascular diseases (CVD) [28]. Importantly, post-mortem examinations of people who died with COVID-19 revealed widespread vascular abnormalities including thrombosis, microangiopathy, and a high degree of angiogenesis [29].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 8146 individuals that were aged 40 and above without AF, current smokers were statistically significantly more likely to present a DTNPV1 in their ECG, which was associated with an increased risk of death [ 87 ]. Also, in 4507 patients without AF, abnormal DTNPV1 was associated with elevated serum cotinine levels [ 88 ].…”
Section: Atrial Myocardium and Tobacco Smokingmentioning
confidence: 99%